Beyond Blame: cultural barriers to medical reporting - Waring, Justin (Elsevier, 2005)
The paper explores the attitudes of medical physicians towards adverse incident reporting in health care, with particular focus on the inhibiting factors or barriers to participation. It is recognised that there are major barriers to medical reporting, such as the ‘culture of blame’. There are, however, few detailed qualitative accounts of medical culture as it relates to incident reporting. Drawing on a 2-year qualitative case study in the UK, this paper presents data gathered from 28 semi-structured interviews with specialist physicians. The findings suggest that blame certainly inhibits medical reporting, but other cultural issues were also significant. It was commonly accepted by doctors that errors are an ‘inevitable’ and potentially unmanageable feature of medical work and incident reporting was therefore ‘pointless’. It was also found that reporting was discouraged by an anti-bureaucratic sentiment and rejection of excessive administrative duties. Doctors were also apprehensive about the increased potential for managers and non-physicians to engage in the regulation of medical quality through the use of incident data. The paper argues that the promotion of incident reporting must engage with more than the ubiquitous ‘culture of blame’ and instead address the ‘culture of medicine’, especially as it relates to the collegial and professional control of quality.